Method for extracting lead-212 and bismuth-212 from the thorium-232 decay series.
Patent Information
- Application Number
- JP2025555383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-09-10
- Filing Date
- 2025-05-28
- Publication Date
- 2026-10-30
AI Technical Summary
【0024】 本発明の有益な効果は、下記の通りである。 本発明では、多数の実験研究を通じて、天然の232Thから212Pb及び212Biを直接、迅速かつ同時に選択的に分離する方法を提供する。本発明は、好ましくはシリカ系陰イオン交換樹脂を使用する。市販されている従来の全有機型の樹脂と比較して、吸着/脱着の速度が速く、カラム圧が低く、水力学的性能が良いなどの利点を有し、特に、212Pb(半減期10.64h)及び212Bi(半減期約1h)のような半減期の短い放射性同位元素の効率的な分離抽出に適している。実験において、ハロゲン媒体中で212Pb及び212Biに対して高い吸着選択性を有し、232Th崩壊系列における他の核種をほとんど吸着しないことを見出した。したがって、このようなシリカ系陰イオン交換樹脂の分離方法によれば、従来のクラウンエーテル系材料を用いて212Pbを分離抽出する方法に存在する多くの欠点を効果的に解決することができる。この方法は、天然の232Th崩壊系列から212Pb及び212Biを選択的に抽出する場合だけでなく、228Ra崩壊系列、228Th崩壊系列、及び224Ra崩壊系列から212Pb及び212Biを選択的に抽出する場合にも適用可能であり、トリウム、ラジウム、アクチノイド、ランタン、バリウム、鉛及びビスマスなどの複雑な系から鉛及びビスマスを選択的に抽出する場合にも適用可能である。
Smart Images

Figure 2026536447000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention belongs to the field of manufacturing medical radioisotopes, and specifically relates to a method for extracting lead 212 and bismuth 212 from the thorium 232 decay series. BACKGROUND ART
[0002] In recent years, the global incidence of cancer has been increasing year by year, and cancer has become a serious threat to human life and health. Medical radioisotopes have important applications in cancer diagnosis and treatment, and are of great significance for ensuring people's life and health and social stability. 212 Pb / 212 Bi is one of the few radioisotopes that can be used in "targeted alpha nuclide therapy" (abbreviated as TAT), and has good effects on the treatment of malignant tumors such as ovarian cancer, pancreatic cancer, prostate cancer and breast cancer. However, its resources are extremely scarce, which 212 imposes strict restrictions on the development and clinical application of Pb (lead) targeted drugs.
[0003] 212 Pb / 212 Bi is 232 a decay daughter nuclide of Th. Separating and extracting Pb / 212 Pb / 212 Bi from natural thorium does not require a nuclear reactor or accelerator, and 232 a sufficient amount of 212 Pb / 212 212Th can be obtained only by the spontaneous decay of Th, so it is expected to fundamentally solve the bottleneck problem of insufficient supply of 212 Pb / 212 Bi around the world. 232 The Th decay series is shown in Figure 1.
[0004] Methods for separating and extracting 212 Pb / 212 Bi from natural thorium are roughly divided into direct separation methods and indirect separation methods. The direct separation method refers to using a highly selective adsorbent to separate Pb and 212 Pb and 212This refers to the direct and selective extraction of Bi for medical use, in contrast to indirect separation methods. 232 From Th 228 Ra is separated, and then, 228 Th, 224 Ra is separated in stages, and finally 224 Ra / 212 Using a Pb generator 212 Pb / 212 This refers to obtaining Bi. Currently, indirect separation methods are widely reported and the technology is relatively mature. 212 Pb / 212 For the widespread distribution and transportation of Bi (the former having a half-life of 10.6 hours), 224 Ra / 212 Using a Pb generator is advantageous. However, this method also has drawbacks. Specifically, the separation process is complex and involves many steps, requiring multiple pauses to allow daughter nuclides to grow, as well as multiple purification and testing of the separation products. This increases the risk of radiation damage to humans (especially from short-lived radioactive gases). 220 This not only leads to increased production costs and longer manufacturing cycles, but also to the protection of Rn.
[0005] In contrast, the direct separation method is simple and efficient, and applies to the administrative regions of cities, counties, and even provinces. 212 Pb / 212 It is very suitable for the centralized distribution and supply of Bi. However, the drawbacks and key aspects of this method are, 212 Pb and 212 Selectively selecting Bi 232 The objective is to find appropriate separation materials and techniques for efficiently separating thorium from the Th decay series. Currently, natural thorium is being separated by solid-phase adsorption (i.e., using Pb resin) using crown ether extractants. 212 Although it has been reported that this method can achieve the goal of selectively separating Pb, 212 The inability to extract Bi simultaneously leads to the wasteful use of rare radionuclide resources. Furthermore, crown ether extractants are very expensive, and they have a certain degree of water solubility, requiring further separation and purification to remove dissolved crown ethers before subsequent pharmaceutical manufacturing. [Overview of the Initiative]
[0006] The technical problem that the present invention aims to solve is to provide a method for extracting lead 212 and bismuth 212 from the thorium 232 decay series that can simultaneously extract lead 212 and bismuth 212, has a fast extraction rate, high purity, and is less likely to cause organic contamination of the product.
[0007] An embodiment of the present invention provides a method for extracting lead 212 and bismuth 212 from the thorium-232 decay series. In this method, a solution containing thorium-232 decay series material is passed through an anion exchange resin column. The solution containing thorium-232 decay series material contains halogen ions, and the hydrogen ion concentration in the solution containing thorium-232 decay series material is greater than 0.01 mol / L (preferably, the hydrogen ion concentration is 0.5 to 2 mol / L). Lead 212 and bismuth 212 are adsorbed by the anion exchange resin column, while other nuclides such as 228Ra, 228Ac, and 232Th pass through the anion exchange resin column without being adsorbed. An eluent is injected to desorb lead 212 and bismuth 212 from the anion exchange resin column, respectively, and separate and extract lead 212 and bismuth 212.
[0008] The aforementioned thorium-232 decay series is the parent nuclide 232 It contains Th, and other decay daughter nuclides at each level, for example. 228 Ra, 228 Ac, 228 Th, 212 Pb, 212 Bi, 208 This further includes Tl, etc. (Figure 1).
[0009] Preferably, the concentration of halogen ions in the solution containing the thorium-232 decay series material is 0.3 to 4 mol / L, and more preferably 0.5 to 2 mol / L.
[0010] Preferably, the thorium-232 decay series material is a thorium salt or a thorium oxide, and more preferably, a soluble salt containing thorium-232.
[0011] Preferably, the thorium salt is thorium nitrate hydrate.
[0012] Preferably, the form of the halogen ion is Cl - , Br - or I - The acid or salt contains, preferably hydrochloric acid, hydrobromic acid, or hydroiodic acid, with a concentration of preferably 0.3 to 4 mol / L, and more preferably 0.3 to 2 mol / L. More preferably, it is hydrobromic acid or hydroiodic acid.
[0013] In solutions containing thorium-232 decay series materials, the anions must not include any other anions in addition to the halogen ions, in a concentration exceeding that of the halogen ions. Otherwise, competitive adsorption will occur, reducing the selective adsorption effect of lead and bismuth.
[0014] When using hydrochloric acid, the concentration of the hydrochloric acid is preferably 0.5 to 3 mol / L, and more preferably 1 to 2 mol / L.
[0015] When using hydrobromic acid, the concentration of hydrobromic acid is preferably 0.3 to 2 mol / L, and more preferably 0.3 to 1 mol / L.
[0016] When using hydroiodic acid, the concentration of hydroiodic acid is preferably 0.5 to 3 mol / L, and more preferably 0.5 to 1 mol / L.
[0017] Preferably, the anion exchange resin is a silica-based anion exchange resin.
[0018] Preferably, the method for producing the silica-based anion exchange resin involves copolymerizing 4-vinylpyridine and divinylbenzene in a porous SiO2 pore in the presence of an initiator and a diluent to obtain silica-based polyvinylpyridine, and then methylating the silica-based polyvinylpyridine with dimethyl sulfate to obtain the silica-based anion exchange resin.
[0019] The initiator is a mixture of azobisisobutyronitrile and 1,1'-azobis(cyclohexanecarbonitride), and the diluent is acetophenone and diethyl phthalate. The volume ratio of 4-vinylpyridine to divinylbenzene is 15-20:5-7.
[0020] The solvent for the methylation reaction is an aqueous methanol solution, with a methanol-to-water mass ratio of 1:1.
[0021] Preferably, the effective particle size of the silica-based anion exchange resin is 37 to 150 μm, and the BET specific surface area is 50 to 80 m². 2 The density is / g, and the average pore size is 10-50 nm.
[0022] Preferably, when separating lead-212, the eluent is an aqueous solution with a salt or acid concentration of less than 0.5 mol / L, and more preferably ultrapure water. When separating bismuth-212, the eluent is a nitric acid solution with a concentration greater than 0.5 mol / L, and more preferably 1-2 mol / L HNO3.
[0023] Preferably, before injecting the eluent, a solution containing halogen ions (preferably hydrochloric acid, hydrobromic acid, or hydroiodic acid, with a concentration of preferably 0.5-1 mol / L) is injected to elute ions other than lead-212 and bismuth-212.
[0024] The beneficial effects of the present invention are as follows: In this invention, through numerous experimental studies, natural 232 From Th 212 Pb and 212 This invention provides a method for directly, rapidly, and simultaneously selectively separating Bi. The present invention preferably uses a silica-based anion exchange resin. Compared to conventional commercially available all-organic resins, it has advantages such as faster adsorption / desorption rates, lower column pressure, and better hydrodynamic performance, and in particular, 212 Pb (half-life 10.64h) and 212It is suitable for the efficient separation and extraction of radioactive isotopes with short half-lives, such as Bi (half-life approximately 1 hour). In experiments, in a halogen medium... 212 Pb and 212 It has high adsorption selectivity for Bi, 232 We found that it hardly adsorbs other nuclides in the Th decay series. Therefore, according to this separation method of silica-based anion exchange resin, using conventional crown ether-based materials 212 This method can effectively overcome many of the shortcomings present in methods for isolating and extracting Pb. 232 From the Th decay series 212 Pb and 212 Not only when selectively extracting Bi, 228 Ra Collapse Series, 228 Th decay series, and 224 From the Ra Collapse series 212 Pb and 212 This method is applicable to the selective extraction of Bi, and also to the selective extraction of lead and bismuth from complex systems such as thorium, radium, actinides, lanthanum, barium, lead, and bismuth.
[0025] The present invention 232 From the solution 212 Pb and 212 This provides a novel method for the direct, rapid, and selective separation of Bi. This method effectively avoids the use of expensive water-soluble crown ether extractants. Results obtained by experimental gamma spectroscopy. 212 The Pb samples were found to have extremely high purity and were demonstrated to be virtually free of impurity radionuclides such as Th, Ac, and Ra.
[0026] The material used in this invention is a silica-based anion exchange resin, which has the advantages of being low-cost, having a fast adsorption / desorption rate, low column pressure, good hydrodynamic performance, and stable chemical properties that make it difficult to dissolve. 232 From the Th decay series 212 Pb and 212 This enables the simultaneous separation and extraction of Bi, thereby maximizing the utilization of rare radionuclide resources.
[0027] In this invention, by using an acidic solution containing halogen ions, the anion exchange resin is 212 Pb and 212 It can simultaneously and rapidly adsorb Bi, and does not adsorb other metal elements. If elution occurs, it is simply a matter of using a different eluent. 212 Pb and 212 We were able to achieve Bi elution, 212 Pb and 212 We achieved the separation of Bi, and the separated product has high purity. [Brief explanation of the drawing]
[0028] [Figure 1] This is the collapse sequence of 232Th and 232U. [Figure 2] This paper compares the adsorption kinetics of SiPyR-N4 resin with those of commercially available anion exchange resins IRA900 and PA316 resin. [Figure 3] This shows the change in TOC content in SiPyR-N4 suspension over time. [Figure 4] This shows the static adsorption behavior of SiPyR-N4 resin to different metal ions in a hydrochloric acid medium. [Figure 5] This paper demonstrates the static adsorption behavior of SiPyR-N4 resin to different metal ions in a hydrobromic acid medium. [Figure 6] This shows the static adsorption behavior of SiPyR-N4 resin to different metal ions in a hydroiodic acid medium. [Figure 7] This shows the static adsorption behavior of SiPyR-N4 resin to different metal ions in a nitric acid medium. [Figure 8] This shows the static adsorption behavior of commercially available IRA900 resins to different metal ions in a hydrochloric acid medium. [Figure 9] This shows the static adsorption behavior of commercially available PA316 resin to different metal ions in a hydrochloric acid medium. [Figure 10] This shows a comparison of the lead elution effects of different eluents. [Figure 11]This paper compares the eluting effects of different eluents on bismuth. [Figure 12] This shows the separation of Pb, Bi from Th, La, and Ba. [Figure 13] This is a comparison of the gamma energy spectra of solid 232Th (a) and the separated 212Pb (b) and 212Bi (c) samples. Figure 13(a) shows the gamma energy spectrum of solid 232Th, Figure 13(b) shows the gamma energy spectrum of the separated 212Pb solution, and Figure 13(c) shows the gamma energy spectrum of the separated 212Bi solution. Explanation of symbols: I: dead volume; II: mixed metal solution; III: 1.0M HCl solution; IV: ultrapure water; V: 1.0M HNO3 [Modes for carrying out the invention]
[0029] Example 1 The anion exchange resin is a silica-based anion exchange resin, and its manufacturing process is divided into two steps. Step 1: Synthesis of silica-based polytetravinylpyridine (SiPyR-N3) First, 100 g of porous SiO2 particles were added to the rotary evaporator flask. The flask was rotated at a low speed. The oxygen gas in the rotary evaporator was replaced twice with nitrogen gas, and then the system was evacuated to 20 hPa. Next, 45 mL of ACP (acetophenone), 30 mL of DEP (diethyl phthalate), 17.69 mL of 4-vinylpyridine, 6.41 mL of DVB (divinylbenzene), 0.3215 g of AIBN (azobisisobutyronitrile), and 0.2144 g of V-40 (1,1'-azobis(cyclohexanecarbonile)) were mixed in this order. After the initiators AIBN and V-40 were completely dissolved, the mixed oil phase was introduced into the rotary evaporator flask by pressure difference. The rotation speed was adjusted, and the oil phase and SiO2 were thoroughly mixed by lightly tapping the flask wall until no obvious aggregates were formed. At this point, it was determined that the oil phase had completely penetrated the SiO2. Nitrogen gas was injected to return to atmospheric pressure, and the temperature was raised to initiate the polymerization reaction. The mixture was heated in an oil bath and maintained at 60°C for 1 hour, 70°C for 2 hours, 80°C for 2 hours, and 90°C for 13 hours. After the reaction was complete, the mixture was washed twice alternately with acetone and ultrapure water. The product was named SiPyR-N3 and dried in a vacuum oven at 40°C for 48 hours.
[0030] Step 2: Production of silica-based anion exchange resin SiPyR-N4 using SiPyR-N3 as a precursor. An appropriate amount of SiPyR-N3 resin and 500 g of methanol / water (mass ratio 1:1) were sequentially added to a 250 mL three-necked flask equipped with a stirring blade and a dropping funnel. The mixture was heated using a water bath and the reaction temperature was maintained at approximately 25°C. Then, three times the molar amount of vinylpyridine contained in the SiPyR-N3 resin in the flask was taken and slowly added to the flask using a dropping funnel while controlling the flow rate. The mixture was stirred at a low speed, and the pH of the solution was adjusted to neutral with a 10 M sodium hydroxide solution. Once the pH of the solution gradually stabilized and stopped changing, twice the molar amount of vinylpyridine contained in the SiPyR-N3 resin in the flask was added. The pH value was continued to be controlled to maintain neutral conditions for the reaction to proceed. After the reaction was complete, the product was named SiPyR-N4 and washed twice alternately with acetone and ultrapure water. Subsequently, SiPyR-N4 was washed with a 5M NaCl solution and ultrapure water to convert it to the chloride form. Finally, the converted SiPyR-N4 was placed in a vacuum oven and dried at 40°C for 48 hours.
[0031] The functional group of the quaternary ammonium-modified strongly basic silica-based anion exchange resin SiPyR-N4 is 1-methylpyridine, the effective particle size is 37-150 μm, the organic component is approximately 25.5%, and the BET specific surface area is approximately 52.2 m². 2 The density was / g, and the average pore size was 36.8 nm.
[0032] Example 2 Experiment comparing the adsorption rates of different resins (1) A certain amount of bismuth nitrate was dissolved in 1.0 M HCl medium to prepare a mixed working solution containing 1.0 M HCl and 500 mg / L Bi. (2) Prepare several clean vials of 40 mL each, and add 0.05 g of the resin from Example 1 to each vial. Then, take 20 mL of the mixed working solution and add it to the vials. Close the lids and seal them, then place them in a 25°C water bath shaker and shake (shaking frequency 120 rpm). (3) Different mixing contact times were set, and the samples that reached the predetermined time were immediately separated into solid and liquid using a microporous filter. (4) After diluting the solutions before and after adsorption with dilute nitric acid to appropriate concentrations, the Bi concentration in the solutions was measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The adsorption efficiency of the resin was calculated according to the concentration difference before and after adsorption, and a time-dependent adsorption dynamic curve of the adsorption efficiency was created. (5) Similarly, the adsorption kinetic curves of commercially available strong basic anion exchange resins IRA900 and PA316 were evaluated using the method described in steps (1)-(4) above, and the adsorption rates were compared.
[0033] IRA900 resin is a commercially available strong basic anion exchange resin manufactured by Dow Chemical Company in the United States. Its skeletal structure is a styrene-divinylbenzene copolymer, and its functional group is a trimethylquaternary ammonium salt.
[0034] PA316 resin is a commercially available strong basic anion exchange resin manufactured by Mitsubishi Plastics, Inc., and its structure and functional groups are identical to those of IRA900 resin.
[0035] The experimental results are shown in Figure 2. The resin in Example 1 basically reached adsorption equilibrium within 10 minutes, while the IRA900 and PA316 resins required more than 120 minutes to reach adsorption equilibrium. The adsorption rate of the resin in Example 1 was significantly faster than that of commercially available anion exchange resins.
[0036] Example 3 Chemical stability experiment of the resin in Example 1 (1) Prepare several clean vials, add 0.1 g of the resin from Example 1 to each vial, then take 30 mL of 1.0 M HCl solution and mix it with the resin, then close the lid and seal. (2) These vials were placed in a 25°C constant temperature water bath shaker and shaken, with the shaking frequency set to 120 rpm. (3) Different mixing contact times were set, and immediately after the predetermined time was reached, the samples were separated into solid and liquid using a microporous filter. (4) The TOC content in the solution was analyzed using a total organic carbon (TOC) analyzer, and a curve showing the change in TOC with contact time was created.
[0037] The experimental results are as shown in Figure 3: there is basically no significant change in the time-dependent increase of the TOC content in the solution, which proves that the resin of Example 1 has good chemical stability and is insoluble in water.
[0038] Example 4 Selective Adsorption Experiment (1) A certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate and barium nitrate were weighed and dissolved in HCl media of different concentrations to prepare a mixed solution containing 100mg / L Th, 90mg / L Pb, 90mg / L Bi, 60mg / L La and 60mg / L Ba. (2) A plurality of clean vials with a volume of 40 mL were prepared, 0.05 g of the resin of Example 1 was added to each vial, and 20 mL of the mixed solution was taken and added to the vial. The vial was capped and sealed, then placed in a 25°C water bath shaker for shaking, with the shaking frequency set to 120 rpm. Here, the stable 207 Pb was 232 used to simulate Pb in the Th decay series. The stable 212 Bi was used to simulate Bi in the Th decay series. La is close to Ac in chemical properties, and 209 Bi was 232 the Th decay series, and 212 was used to simulate Ac in the Th decay series. Ba is close to Ra in chemical properties, and 232 the Th decay series, and 228 was used to simulate Ac. Ba is close to Ra in chemical properties, 232 the Th decay series, and 224 Ra and 228 Ra in the Th decay series was simulated using it. (3) After shaking for 2 h, the sample was subjected to solid-liquid separation with a microporous filter. (4) After diluting the solutions before and after adsorption to appropriate concentrations with dilute nitric acid, the concentration of each metal element in the solution was measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The adsorption efficiency of the resin for different metal elements was calculated according to the concentration difference of each metal element before and after adsorption. (5) In the same manner as the above steps (1-4), the adsorption behavior of SiPyR-N4 resin in hydrobromic acid and hydroiodic acid media was investigated.
[0039] The experimental results are shown in Figures 4, 5, and 6. The resin of Example 1 showed specific adsorption selectivity for Pb and Bi in all three acidic media, but did not adsorb Th, Ba, and La.
[0040] As can be seen from Figure 4-6, in the case of static adsorption, the anion exchange resin mainly adsorbed Bi and a small amount of Pb in the hydrochloric acid medium, but basically did not adsorb other ions such as La, Th, and Ba. In the hydrobromic acid medium, the resin mainly adsorbed Bi and Pb, but the adsorption effect at low concentrations of hydrobromic acid was higher than that at high concentrations, and when it exceeded 3 mol / L, the resin's adsorption effect on Bi and Pb decreased. In the hydroiodic acid medium, the resin also mainly adsorbed Bi and Pb, and the adsorption effect at low concentrations of hydroiodic acid was higher than that at high concentrations, and when it exceeded 2 mol / L, the resin's adsorption on Bi and Pb decreased.
[0041] Comparative Example 1 Compared to Example 4, the procedure is the same as in Example 4, except that in step (1), a certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate, and barium nitrate are weighed and dissolved in HNO3 media of different concentrations.
[0042] The experimental results are shown in Figure 7, which means that silica-based anion exchange resins do not adsorb any metal ions in the HNO3 medium, and therefore cannot achieve selective separation of lead and bismuth. In other words, Example 4 is more suitable for the selective separation of lead and bismuth in a solution system compared to Comparative Example 1.
[0043] Example 5 Comparative experiment of the adsorption behavior of different anion exchange resins for thorium, lead, bismuth, lanthanum, and barium in a hydrochloric acid medium. (1) A certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate, and barium nitrate was weighed and dissolved in HCl media of different concentrations to prepare a mixed solution containing 100 mg / L of Th, 90 mg / L of Pb, 90 mg / L of Bi, 60 mg / L of La, and 60 mg / L of Ba. (2) Several clean vials of 40 mL volume were prepared, 0.05 g of IRA900 resin was added to each vial, and 20 mL of the mixed solution was taken and added to the vials. The vials were sealed with lids and placed in a 25°C water bath shaker and shaken at a shaking frequency of 120 rpm. (3) After shaking for 2 hours, the sample was separated into solid and liquid using a microporous filter. (4) After diluting the solutions before and after adsorption with dilute nitric acid to an appropriate concentration, the concentration of each metal element in the solution was measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The adsorption efficiency of the resin for different metal elements was calculated according to the difference in concentration of each metal element before and after adsorption. (5) The adsorption behavior of IRA900 resin and PA316 resin in hydrochloric acid medium was investigated in the same manner as in steps (1-4) above, and compared with the adsorption behavior of SiPyR-N4 to the above metal elements.
[0044] The experimental results are shown in Figures 8 and 9, and all three anion exchange resins manufactured by different companies exhibited the same adsorption behavior. That is, under the experimental conditions, they can selectively adsorb to both lead and bismuth, thus, 232 In the Th decay series 212 Pb and 212 It can be used for the selective separation of Bi.
[0045] Example 6 Lead leaching experiment (1) A small amount of SiPyR-N4 resin from Example 1 was taken and packed into a glass adsorption column with specifications of φ×h=5mm×50cm. (2) A bottom-up flow mode was adopted, and ultrapure water was first introduced to remove air bubbles, and the flow rate was adjusted to 1.0 mL / min. (3) The resin gallum was pretreated by introducing 50 mL of 1.0 M HCl. (4) A certain amount of lead nitrate was weighed and dissolved in 1.0 M HCl medium to prepare a hydrochloric acid solution containing 90 mg / L of Pb. (5) After introducing approximately 45 mL of the above lead solution, 50 mL of ultrapure water was introduced, and the lead concentration in the effluent was measured by ICP-AES. (6) The above steps (1-4) were repeated, and the ultrapure water in step (5) was adjusted to 0.1 M HCl and 0.01 M HCl, respectively, and the lead elution effect of the ultrapure water and the dilute acid solution was compared.
[0046] The experimental results are shown in Figure 10, demonstrating that ultrapure water can dissolve lead more easily and achieve a higher concentration ratio compared to 0.1M HCl and 0.01M HCl.
[0047] Example 7 Bismuth elution experiment (1) A small amount of SiPyR-N4 resin from Example 1 was taken and packed into a glass adsorption column with specifications of φ×h=5mm×50cm. (2) A bottom-up flow mode was adopted, and ultrapure water was first introduced to remove air bubbles, and the flow rate was adjusted to 1.0 mL / min. (3) The resin gallum was pretreated by introducing 50 mL of 1.0 M HCl. (4) A certain amount of lead nitrate was weighed and dissolved in 1.0 M HCl medium to prepare a hydrochloric acid solution containing 90 mg / L of Bi. (5) After introducing approximately 45 mL of the above Bi solution, 100 mL of 1.0 M HNO3 solution was introduced, and the Bi concentration in the effluent was measured by ICP-AES. (6) Repeat steps (1-4) above, and replace the ultrapure water in step (5) with 3M HNO3 and 0.1M HNO3, respectively, and compare the elution effect of 1.0M HNO3 and nitrate solutions of other concentrations on bismuth.
[0048] The experimental results are shown in Figure 11. Compared to 3.0 M HNO3, 0.1 M HNO3, and 1.0 M HNO3, Bi can be eluted more easily, and a higher concentration ratio can be achieved. Conversely, 0.1 M HNO3 cannot achieve complete elution of Bi.
[0049] Example 8 Cold-formed separation simulation experiment (1) A small amount of the resin from Example 1 was taken and packed into a glass adsorption column with specifications of φ×h=5mm×50cm. (2) A bottom-up flow mode was adopted, and ultrapure water was first introduced to remove air bubbles, and the flow rate was adjusted to 1.0 mL / min. (3) The resin gallum was pretreated by introducing 50 mL of 1.0 M HCl. (4) A certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate, and barium nitrate was weighed and dissolved in 1.0 M HCl medium to prepare a mixed solution containing 100 mg / L of Th, 90 mg / L of Pb, 90 mg / L of Bi, 60 mg / L of La, and 60 mg / L of Ba. (5) Approximately 45 mL of the above mixed solution was introduced. At this time, Pb and Bi were fixed to the resin column simultaneously, while other elements, such as thorium, lanthanum, and barium, passed directly through the resin column. (6) 15 mL of 1.0 M HCl solution was passed through the resin column to elute the thorium, lanthanum, and barium remaining on the column. (7) 25 mL of ultrapure water was passed through the resin column to desorb the Pb adsorbed onto it. (8) 50 mL of 1.0 M HNO3 solution was passed through the resin column to desorb the Bi immobilized on the resin column. (9) Effluent was collected using a fraction collector, and the collection time for each centrifuge tube was set to 5 minutes. The concentration of each metal element in each centrifuge tube was measured using ICP-AES.
[0050] The experimental results are shown in Figure 12. The resin column of Example 1 was able to selectively immobilize Pb and Bi in the mixed metal solution, but did not adsorb Th, Ba, and La. Pb and Bi were successfully separated from the Th solution and recovered individually.
[0051] Example 9 Hot separation experiment (1) A small amount of the resin of Example 1 was taken and filled into a glass adsorption column with a specification of φ×h=5mm×50cm to fully pack it. (2) A bottom-up flow mode was adopted, ultrapure water was first introduced to discharge air bubbles, and the flow rate was adjusted to 1.0 mL / min. (3) 50 mL of 1.0 M HCl was introduced to pretreat the resin column. (4) 2.0 g of water and thorium nitrate were weighed and dissolved in 45 mL of 1.0 M HCl medium. (5) About 45 mL of the above mixed solution was passed through. At this time, Pb and Bi were simultaneously immobilized on the resin column, while other elements, such as thorium, actinium and radium, directly passed through the resin column. (6) 15 mL of 1.0 M HCl solution was passed through to elute residual thorium, actinium and radium remaining in the resin column. (7) 25 mL of ultrapure water was passed through to desorb the Pb adsorbed on the resin column 212 . (8) 50 mL of 1.0 M HNO₃ solution was passed through to desorb the Bi immobilized on the resin column 212 . (9) The collected Pb sample was taken for gamma-ray spectral analysis 212 , and compared with the gamma spectrum of Th. 232 The Th concentration in the Pb sample was analyzed by ICP-AES. 212
[0052] The experimental results are as shown in Figure 13. Compared with the gamma energy spectrum peak of solid Th 232 , the gamma energy spectrum peaks of the Pb and Bi sample nuclides obtained in the present invention are fewer 212 212 , the trace amounts of Ra and Ac present in the Th decay series are not completely removed 232 224 228 , Pb and Bi are basically retained and have relatively high purity. As can be seen from the measurement results of ICP-AES 212 212 212 Pb and 212 The thorium concentration in the Bi sample solution was 0 mg / L, which is lower than the detection limit of the instrument. 232 Th and 228 It was proven that Th was completely removed. Therefore, together with Example 4, the experiment showed that this method is 232 From the Th decay series 212 Pb and 212 It was proven that Bi can be selectively and directly extracted.
[0053] Those skilled in the art will understand that the discussion of each of the above embodiments is merely illustrative, and that the scope of protection of this application is not intended to be limited to these examples. Under the spirit of this application, technical features of the above embodiments or different embodiments may be combined, and the steps can be implemented in any order. It should be understood that many other variations exist for one or more different aspects of the above embodiments, but are not shown in detail for clarity.
[0054] One or more embodiments in this application are intended to cover all such substitutions, modifications, and variations that fall within the broad scope of this application. Accordingly, any omissions, modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and principles of one or more embodiments in this application should be included within the scope of protection of this application.
Claims
1. A method for extracting lead 212 and bismuth 212 from the thorium-232 decay series, A method characterized by passing a solution containing thorium-232 decay series material through an anion exchange resin column, wherein the solution containing thorium-232 decay series material contains halogen ions, the hydrogen ion concentration in the solution containing thorium-232 decay series material is greater than 0.01 mol / L, lead 212 and bismuth 212 are adsorbed by the anion exchange resin column, other nuclides pass through the anion exchange resin column without being adsorbed, and an eluent is injected to desorb lead 212 and bismuth 212 from the anion exchange resin column, and then separating and extracting them to obtain lead 212 and bismuth 212.
2. The method according to claim 1, characterized in that the concentration of halogen ions is 0.3 to 4 mol / L.
3. The method according to claim 1, characterized in that the thorium-232 decay series material is a thorium salt or a thorium oxide.
4. The method according to claim 3, characterized in that the thorium salt is thorium hydrated nitrate.
5. The form in which halogen ions exist is Cl - , Br - Or I - The method according to claim 1, characterized in that it is an acid or salt containing an acid.
6. The method according to any one of claims 1 to 5, characterized in that the anion exchange resin is a silica-based anion exchange resin.
7. The method for producing the silica-based anion exchange resin involves using 4-vinylpyridine and divinylbenzene in the presence of an initiator and a diluent in porous SiO 2 The method according to claim 6, characterized in that silica-based polyvinylpyridine is obtained by copolymerizing an in-situ solution within the pores, and the silica-based polyvinylpyridine is methylated to obtain the silica-based anion exchange resin.
8. The effective particle size of the silica-based anion exchange resin is 37 to 150 μm, and the BET specific surface area is 50 to 80 m². 2 The method according to claim 6, characterized in that the amount is / g and the average pore diameter is 10 to 50 nm.
9. The method according to any one of claims 1 to 5, characterized in that when separating lead-212, the eluent is an aqueous solution with a salt or acid concentration of less than 0.5 mol / L, and when separating bismuth-212, the eluent is a nitric acid solution with a concentration of more than 0.5 mol / L.
10. The method according to claim 9, characterized in that when separating lead-212, the eluent is ultrapure water, and when separating bismuth-212, the eluent is 1.0 M nitric acid.
